The effectiveness of boards of directors in two-tier board system: Evidence from Vietnamese-listed enterprises - Tran, Quan; Koufopoulos, Dimitrios N.; Warner, Bernadette (Journal of Eastern European and Central Asian Research (JEECAR), 2014)
<span style="font-size: 12.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB"> This paper presents several theories to achieve a better understanding of corporate governance structures and their operations in a two-tier-board corporate governance structure. The author also analyses transitional economies using the case of Vietnam. The author investigates the influence of independent directors upon the probability of CEO turnover as well as the sensitivity of the link between performance and turnover. The findings show that non-executive directors are not always independent. At the same time, independent directors have a vital role to play in making decisions concerning CEO dismissal. These directors also reduce the effects of CEO ownership and CEO duality upon the probability of CEO turnover. In summation, the research found that performance and CEO age constitute key factors in CEO turnover, regardless of the corporation or board size. <!– st1\:*behavior:url(#ieooui) –>